BASIC RESEARCH:Carrier selection for bone marrow mesenchymal stem cells transplantation in periodontal regeneration: calcium alginate or fibrin gel? - Tan, Zhen; Zhao, Qing; Gong, Ping; Zhang, Jinchao; Liao, Dapeng; Yuan, Quan; Wei, Na (Archives of Medical Science, 2009)
Introduction: The aim of the present study is to find a more suitable carrier for bone marrow mesenchymal stem cells (BMSCs) transplantation to promote periodontal regeneration. Material and methods: Bone marrow mesenchymal stem cells were cultivated in the presence of calcium alginate or fibrin glue. Cell viability was investigated using Vi-CELLTM after incubation for 30 and 60 min at room temperature. Cell proliferation was investigated with the MTT method. Cell adhesion and morphology were detected by scanning electron microscopy after co-culture with fibrin glue or alginate gel for 24 and 48 h. The osteogenic differentiation marker (ALP) of BMSCs was measured as well. Results: The viability rate of BMSCs declined after cells were mixed with both calcium alginate and fibrin gel. Both carriers inhibited cell proliferation and spreading, but these effects became weaker with time. ALP expression in BMSCs was not significantly different between the calcium alginate group and a control group, but increased after incubated with fibrin glue. Conclusions: Considering these factors, the potential immunological rejection risk of fibrin glue, and the advantages of calcium alginate in simple manipulation and lessened interference, calcium alginate might be more suitable as a cell-carrier for bone marrow mesenchymal stem cells transplantation in periodontal regeneration.